Preliminary study survey of student needs in learning plant morphology towards a more effective learning model - Zuchrotus Salamah; Ika Maryani; Tri Kinasih Handayani (JURNAL BIOEDUKATIKA, 2025)
Plant morphology plays a crucial role in biological education, yet it often faces challenges regarding the effectiveness of its learning models. This preliminary study aims to identify student needs in plant morphology learning. A survey method was used to collect data on student opinions, understanding, difficulties, and attitudes after completing the plant morphology course through a questionnaire. The study was conducted from December 2024 to January 2025. The sample selection used a purposive sampling technique, with 128 respondents consisting of Biology and Biology Education students at UAD. Data were collected using a Google Form-based questionnaire. Research variables were measured using a Likert scale, along with binary yes/no options to assess respondents' agreement with various statements, as well as several open-ended questions. The study results show that 99% of students consider plant morphology an important course. However, students still find difficulties in learning plant morphology, particularly in the topics of flower parts, floral formulas, and floral diagrams (55.5%). The study found that students prefer environmental learning resources to better master the material. Practical and observational methods were selected by 84% of students as preferred learning. Furthermore, 90% of students emphasized the importance of outdoor learning experiences due to direct involvement with nature, and 86% expressed willingness to participate. Thus, it can be concluded that a learning model incorporating outdoor experiences is needed for plant morphology courses